Assessing the clinical utility of Wnt pathway markers in colorectal cancer. - Veloudis, Georgios; Pappas, Apostolos; Gourgiotis, Stavros; Falidas, Evangelos; Dimitriou, Nikoletta; Karavokiros, Ioannis; Aggelou, Anastasios; Komborozos, Vasileios; Petraki, Constantina; Menounos, Panagiotis; Bramis, Ioannis; Bastounis, Elias; et al. (J BUON, 2017)
PURPOSE: β-catenin and AXIN2 play an important role in the Wnt signaling pathway. The aim of this study was to investigate β-catenin and AXIN2 expression in colorectal cancer (CRC) and relate these findings with patients' clinicopathological features and prognosis. METHODS: 57 consecutive patients with surgically treated CRC were included in this study. Quantitative PCR and immunohistochemistry (IHC) analyses were performed to characterize the expression of the aforementioned markers in CRC tissues. RESULTS: β-catenin overexpression in the nucleus was associated with advanced N stage CRCs (p=0.04). Multivariate Cox regression analysis showed that β-catenin overexpression is an independent prognostic factor for overall survival (OS). A positive correlation between β-catenin location and AXIN2 mRNA was observed. CONCLUSIONS: Nuclear β-catenin is a valuable prognostic factor. AXIN2 is a component of the "Destruction Complex" and also a Wnt target gene. However, the clinical importance of AXIN2 expression in CRC remains unclear.